Estratégias ou táticas alternativas: procurando novos caminhos para a promoção da saúde entre modelos assistenciais e processos de trabalho - Bezerra, Italla Maria Pinheiro (2011)
The objective was to understand the characteristics of models of health care from the acts and actions of physicians and nurses, the family health teams of health districts I and II, the city of Joao Pessoa, identifying alternative strategies or tactics produced by these professionals. This is an exploratory, descriptive and inferential, developed from qualitative and quantitative approaches, held in the city of João Pessoa, in the period from February to November 2010. This research was divided into two sequential phases: the first included the collection of data through a questionnaire applied to doctors and nurses of Districts I and II, and the second concerning the qualitative phase, conducted by semistructured interview for professionals health have developed some alternative strategy or tactic in their professional practices. We used the Hypothesis Test as a method of Decision Making and Technical Analysis of Discourse proposed by Fiorin (2008) for empirical analysis, aimed at the construction of empirical categories, representing every element of the work process. It was evident that health districts I and II show a distribution of physicians and nurses with similarities in relation to aspects: training, time undergraduate, graduate, area of interest to postgraduate students and encourage continuing education. Moreover differences were observed regarding gender, age, area of postgraduate uptime in Primary Care, service time at the Health Unit, Office of another activity and socioeconomic profile. The results showed a higher proportion of these professionals implementing acts and actions characteristic of health care models and Privativist Sanitarian. By analyzing the characteristics of the FHS model, it was found that most doctors and nurses, at least in the field of intention, implements health acts with a view to consolidate the principles and guidelines of this model. Regarding the development of alternative strategies or tactics, only three acts of health professionals have developed which, although not flag something innovative, it reveals a concern to overcome practices of previous models, the prospect of changing the work process.